2003
DOI: 10.4049/jimmunol.171.10.5396
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Subset of Human NK Cells upon Contact with Plasmodium falciparum-Infected Erythrocytes

Abstract: Human NK cells are the earliest source of the protective cytokine IFN-γ when PBMC from nonimmune donors are exposed to Plasmodium falciparum-infected RBC (iRBC) in vitro. In this study, we show that human NK cells form stable conjugates with iRBC but not with uninfected RBC and that induction of IFN-γ synthesis is dependent on direct contact between the NK cell and the iRBC. NK cells respond to iRBC only in the presence of a source of IL-12/IL-18 and the subset of NK cells that preferentially respond to iRBC e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
184
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(208 citation statements)
references
References 36 publications
22
184
0
2
Order By: Relevance
“…This in vivo heterogeneity confirms the relevance of similar findings from in vitro studies (25,36) (K. C. Newman, D. S. Korbel, and E. M. Riley, submitted for publication). Furthermore, data generated from this longitudinal study of prepatent malaria infection have generated a number of novel hypotheses that warrant further investigations in vitro.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This in vivo heterogeneity confirms the relevance of similar findings from in vitro studies (25,36) (K. C. Newman, D. S. Korbel, and E. M. Riley, submitted for publication). Furthermore, data generated from this longitudinal study of prepatent malaria infection have generated a number of novel hypotheses that warrant further investigations in vitro.…”
Section: Discussionsupporting
confidence: 75%
“…Accordingly, associations have been reported between circulating levels of IL-12 and IL-18 and risk of severe Plasmodium falciparum malaria (14, 16 -21), and, in a prospective epidemiological study, IL-12 production was positively associated with IFN-␥ and TNF-␣ production and negatively associated with parasitemia (22). However, although an essential role has been shown for IL-12 in P. falciparum-induced IFN-␥ production from human PBMC and NK cells (23)(24)(25), it has proved very difficult to detect IL-12 in vitro and little is known of its cellular origins. Evidence also suggests that both TGF-␤ and IL-10 can be produced very rapidly, from innate sources, during murine malaria infections and are required to down-regulate potentially pathogenic inflammatory responses once parasitemia is brought under control (26 -28); however, in both mice and humans, excessive concentrations of TGF-␤ and IL-10 early in infection inhibit type-1 immune responses and thus facilitate parasite growth (29,30).…”
Section: R Esearch On the Immunology Of Malaria Infection Has Beenmentioning
confidence: 90%
See 2 more Smart Citations
“…33,34 NK cells are among the first blood cells to produce interferon-g in response to P. falciparum-infected red blood cells, and this production requires contact between NK cells and P. falciparuminfected red blood cells. 35,36 The NK receptors and the parasite ligands that are involved in the NK activation are poorly known. Recently, Mavoungou et al 18 reported that NKp30 binds to PfEMP-1 at the surface of infected red blood cells, and that this interaction mediates cytolysis of P. falciparum-infected red blood cells.…”
Section: Hbc and Immune Genes In Human Malariamentioning
confidence: 99%